ChemInform Abstract: Organocatalytic Enantio‐ and Diastereoselective Conjugate Addition to Nitroolefins: When β‐Ketoamides Surpass β‐Ketoesters. Issue 52 (29th December 2014) - Du, Haiying; Rodriguez, Jean; Bugaut, Xavier; Constantieux, Thierry
Abstract Optimized conditions including a chiral squaramide catalyst render possible the conjugate addition of β‐ketoamides to nitroolefins to give the corresponding products with high diastereoselectivities and excellent enantioselectivities.